Simulation and optimization of irrigation schedule for summer maize based on SWAP model in saline region - Pan, Yanxin; Yuan, Chengfu; Jing, Siyuan (International Journal of Agricultural and Biological Engineering, 2020)
In order to explore the appropriate irrigation schedule for summer maize, a field experiment was conducted in 2013 in Lubotan of Shaanxi Province. Soil water content, soil salinity, soil hydraulic parameters, crop growth parameters and summer maize yield were measured in the experiment. The SWAP model was calibrated based on field experiment observation data in 2013. The SWAP model was used to simulate and optimize irrigation schedule for summer maize after calibration. The results showed that model simulation results of soil water content, soil salinity and summer maize yield agreed well with the measured values. The Root Mean Square Error (RMSE) and Mean Relative Error (MRE) were within the allowable error ranges. The RMSE values were all lower than 0.05 cm3/cm3 and the MRE values were lower than 15% in soil water content calibration. The RMSE values were all lower than 0.1 mg/cm3 and the MRE values were lower than 20% in soil salinity calibration. The RMSE and MRE values were 1299.6 kg/hm2 and 15.26% in summer maize yield calibration. The model parameters suitable for the study area were obtained in calibration. The SWAP model could be used to simulate and optimize irrigation schedule for summer maize after calibration. The SWAP model was used to simulate soil water-salt balance, summer maize yield and water use efficiency under different irrigation schedules. The model simulation results for different irrigation schedules indicated that the optimal irrigation schedules of summer maize were three times each for jointing stage (July 5), heading stage (August 5) and grain filling stage (August 30) with irrigation amount of 128 mm, 128 mm and 96 mm, respectively. The optimal irrigation quota was 352.0 mm for summer maize in the study area. Keywords: SWAP model, summer maize, irrigation schedule, saline region, Lubotan DOI: 10.25165/j.ijabe.20201303.5218 Citation: Pan Y X, Yuan C F, Jing S Y. Simulation and optimization of irrigation schedule for summer maize based on SWAP model in saline region. Int J Agric & Biol Eng, 2020; 13(3): 117–122.